Electrospun polycaprolactone nanofibres decorated by drug loaded chitosan nano- reservoirs for antibacterial treatments - Guarino, V; Cruz-Maya, Iriczalli; Altobelli, Rosaria; Abdul Khodir, Wan Khartini; Ambrosio, Luigi; Alvarez Pèrez, Marco A; Almaguer Flores, Argelia (IOP Publishing, 2017)
The main limitation of conventional antibiotic therapies concerns the low efficacy to fight bacteria attacks during long treatment times. In this context, the integrated use of electrofluidodynamics (EFDs)—basically electrospinning and electrospraying—may represent an interesting route for designing nanostructured platforms with controlled release to prevent the formation of bacterial biofilms in oral implant sites. They allow for the deposition of nanofibres and nanoparticles by different modes—i.e. sequential, simultaneous—for the fabrication of more efficacious systems in terms of degradation protection, pharmacokinetic control and drug distribution to the surrounding tissues. Herein, we will investigate EFDs processing modes and conditions to decorate polycaprolactone nanofibres surfaces by chitosan nano-reservoirs for the administration of Amoxicillin Trihydrate as an innovative antibacterial treatment of the periodontal pocket.